Cypherpunk ethics : radical ethics for the digital age - Anderson, Patrick D. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Cypherpunk Ethics explores the moral worldview of the cypherpunks, a movement that advocates the use of strong E- or crypto, for short - to defend individual privacy and promote institutional transparency in the digital age. Focusing on the writings of Timothy May and Julian Assange, two of the most prolific and influential cypherpunks, the book examines two competing paradigms of cypherpunk philosophy--crypto anarchy and crypto justice--and examines the implications of cypherpunk ethics for a range of contemporary moral issues, including surveillance, privacy, whistleblowing, cryptocurrencies, journalism, democracy, censorship, intellectual property, and power. Rooted in theory but with very real applications, this volume will appeal not only to students and scholars of digital media, communication, journalism, philosophy, political science, critical data studies, sociology, and the history of technology but also to technologists and activists around the world"--
Crypto! -- Cypherpunk meta-ethics -- Cypherpunk theories of the state -- Privacy for the weak -- Transparency for the powerful -- Information wants to be free.
Keywords: Internet -- Moral and ethical aspects; Hacktivism; Data encryption (Computer science) -- Moral and ethical aspects; Data privacy; Transparency in government; Intellectual property; Information policy; PHILOSOPHY / Ethics & Moral Philosophy